The Use of Animated Video-Based Media in Indonesian Drama Studies Courses as an Effort to Adapt Literary Learning during COVID-19Learning - Een Nurhasanah; Uah Maspuroh; Adhi Rizal (International Journal of Educational Excellence and Innovation, 2024)
The application of learning media is one of the main factors in the learning process, especially in the face of pandemics. There needs to be innovation to strive for learners to continue effectively, one of which is by conducting research related to the use of animated video-based media in Indonesian Drama Studies courses to learn literature during covid 19 at the college level. The purpose of this study is to 1) find out the use of animation video-based learning media in Indonesian Drama Studies courses during the Covid 19 pandemic, 2) describe the results of the use of animation video-based learning media in Indonesian Drama Studies courses during the Covid 19 pandemic. The method used is a descriptive qualitative method. It is expected that the existence of animated video learning media helps to distance learning efficiently.